2009
DOI: 10.1074/jbc.m808028200
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Binds to Extracellular Sites on the Plasma Membrane of Plant Cells and Elicits a Rise in Intracellular Calcium Concentration

Abstract: Calmodulin (CaM) is a highly conserved intracellular calcium sensor. In plants, CaM also appears to be present in the apoplasm, and application of exogenous CaM has been shown to influence a number of physiological functions as a polypeptide signal; however, the existence and localization of its corresponding apoplasmic binding sites remain controversial. To identify the site(s) of action, a CaM-conjugated quantum dot (QD) system was employed for single molecule level detection at the surface of plant cells. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
(20 reference statements)
0
25
0
1
Order By: Relevance
“…With ion imaging, Shang et al (2005) first showed that extracellular addition of purified cauliflower CaM stimulates Ca 2+ entry into pollen grains. In an extension of that study, Wang et al (2009) report that the quantum dot‐CaM probe also stimulates Ca 2+ influx. In parallel with results noted above, Shang et al (2005) further show that application of a CaM anti‐serum, or the CaM antagonist W‐7, inhibits the increase in intracellular Ca 2+ .…”
Section: Ca2+ At the Pm/cell Wall Interfacementioning
confidence: 84%
“…With ion imaging, Shang et al (2005) first showed that extracellular addition of purified cauliflower CaM stimulates Ca 2+ entry into pollen grains. In an extension of that study, Wang et al (2009) report that the quantum dot‐CaM probe also stimulates Ca 2+ influx. In parallel with results noted above, Shang et al (2005) further show that application of a CaM anti‐serum, or the CaM antagonist W‐7, inhibits the increase in intracellular Ca 2+ .…”
Section: Ca2+ At the Pm/cell Wall Interfacementioning
confidence: 84%
“…Its presence is suggested in other organellar membranes as well (Schiott et al, 2004;Ali et al, 2007). Its extracellular functions are also reported (Chen et al, 2004;Li et al, 2009;Wang et al, 2009). CaM-binding proteins are versatile in nature and include kinases, cytoskeletal proteins, metabolic enzymes, TFs, channels and pumps, and many proteins of unknown function (Bouche et al, 2005;Ikura & Ames, 2006).…”
Section: Cam and CML Proteinsmentioning
confidence: 89%
“…The high level of cytosolic Ca 2+ was maintained for several minutes [44]. The prolonged rise in cytosolic Ca 2+ (several minutes or longer) was also observed in response to different stimulus when single wavelength, non-ratiometric dyes were used as Ca 2+ indicator, such as Fluo-3, Calcium Green [58][59][60]. Moreover, cell-and stimulus type-specific intracellular free Ca 2+ signals were reported in Arabidopsis, in which a prolonged elevation (several minutes) of cytosolic Ca 2+ was observed in guard cells [61].…”
Section: Nacl-triggered Vacuolar Ca 2+ Release Is Evoked By Ip 3 and mentioning
confidence: 99%